LEGAL PROTECTION FOR CHILDREN IN THE CRIME OF THEFT - Agustri Heriyanto; Erwin Owen Hermansyah; Dwi Atmoko (UNISSULA, 2022)
The purpose of this research is to find out and analyze the legal protection for children as perpetrators of the crime of theft and the obstacles faced in realizing legal protection for these children. the approach method uses a normative juridical approach. The results of the research stated that legal protection for children in conflict with the law can be found in national instruments as follows: the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 concerning Human Rights, Law Number 4 of 1979 concerning Child Welfare, Law Number 35 of 2014 concerning child protection, Law Number 11 of 2012 concerning the Child Criminal Justice System. Then in protecting children as perpetrators of the crime of theft, a diversion system is also implemented. Diversion is a form of protection for children as perpetrators of the crime of theft which must or must be carried out. In practice, the success of legal protection for children in the implementation process of children as perpetrators of the crime of theft is not solely related to the applicable law, but it is also very dependent on the constraints that affect its implementation.